The Role of France National School of Administration in Training of Senior Public Servants and Its Removal - Özmen, Bedrettin (Fırat University, 2023)
The training of senior public employees and managers in the public sector emerges as a subject in which countries carry out different policies in order to respond more effectively and agilely to the ever-changing and increasing needs and expectations of the public. Therefore, it is not suprising that some schools are distinguished in educating senior public officials that modern states need for public administration. The French National School of Administration, which had been operating in France since 1945, was an establishement known for its success in raising qualified senior public administrators and its contribution of the centrist management approach to the French bureaucracy. The school still inspires the models of education of the senior public officials in the developing countries. In this study, the role of the school in French bureaucracy and the factors that ensured its success, its duties, selection and education system, and its closure process is examined. As a specialized institution in training of high level civil servants, the criticisms about the social profiles of its students is also mentioned. The new high-level civil servants mission of France, the country’s changing public service policies, and the qualities and the duties of the new State Institute of Civil Service which replaced the former National School of Administration, are also evaluated.

Kamuda çalışan üst düzey yöneticilerin yetiştirilmesi, kamunun sürekli değişen ve artan ihtiyaç ve beklentilerine daha etkin, daha çevik cevap verebilmek adına ülkelerin kendilerine özgü politikalar yürüttüğü bir alandır. Bu nedenle, modern devletlerin kamu idaresinde ihtiyaç duydukları yöneticilerin yetiştirilmesini sağlamak üzere belli okulların ön plana çıkması şaşırtıcı değildir. 1945 yılından bu yana Fransa’da faaliyet gösteren Fransa Ulusal Yöneticilik Okulu (Ecole National Administration), nitelikli üst düzey kamu yöneticisi yetiştirmede, merkeziyetçiliğin hâkim olduğu Fransa bürokrasisinde önemli bir işleve sahiptir. Gelişmekte olan ülkeler, yöneticilerinin eğitimi ve yetiştirilmesi için zaman zaman bu okuldan esinlenmektedir. Bu çalışmada Ulusal Yöneticilik Okulu tanıtılacak; okulun Fransız bürokrasisindeki rolü ve başarısının ardındaki faktörler, görevleri, öğrenci kabulü ve eğitim sistemi ile kapatılmasındaki süreçler incelenecektir. Üst düzey kamu yöneticilerinin yetiştirilmesinde uzmanlaşmış bir kurum olarak öğrencilerinin zamanla belirginleşen sosyal profilleri ile ilgili eleştirilere değinilecektir. Ayrıca Fransa’nın yeni üst düzey kamu çalışanları misyonu, Fransa’nın değişen kamu hizmetleri politikası ve kapatılan Ulusal Yöneticilik Okulu’nun yerine açılan Ulusal Kamu Hizmetleri Enstitüsü’nün niteliği ve görevleri incelenecektir.
FRANSA ULUSAL YÖNETİCİLİK OKULU’NUN ÜST DÜZEY KAMU YÖNETİCİSİ YETİŞTİRMEDE YERİ VE KAPATILMASI SÜRECİ
Keywords: Political Science (Other); Siyaset Bilimi (Diğer)